Distinct patterns of novel gene mutations in poor-prognostic stereotyped subsets of chronic lymphocytic leukemia: the case of SF3B1 and subset #2 - Strefford JC; Sutton LA; Baliakas P; Agathangelidis A; Malčíková, Jitka; Plevová, Karla; Scarfo L; Davis Z; Stalika E; Cortese D; Cahill N; Pedersen LB; et al. (Leukemia, 2013)
Recent studies have revealed recurrent mutations of the NOTCH1, SF3B1 and BIRC3 genes in chronic lymphocytic leukemia (CLL), especially among aggressive, chemorefractory cases. Nevertheless, it is currently unknown whether their presence may differ in subsets of patients carrying stereotyped B-cell receptors and also exhibiting distinct prognoses. Here, we analyzed the mutation status of NOTCH1, SF3B1 and BIRC3 in three subsets with particularly poor prognosis, that is, subset #1, #2 and #8, aiming to explore links between genetic aberrations and immune signaling. A remarkably higher frequency of SF3B1 mutations was revealed in subset #2 (44%) versus subset #1 and #8 (4.6% and 0%, respectively; P<0.001). In contrast, the frequency of NOTCH1 mutations in subset #2 was only 8%, lower than the frequency observed in either subset #1 or #8 (19% and 14%, respectively; P=0.04 for subset #1 versus #2). No associations were found for BIRC3 mutations that overall were rare. The apparent non-random association of certain mutations with stereotyped CLL subsets alludes to subset-biased acquisition of genomic aberrations, perhaps consistent with particular antigen/antibody interactions. These novel findings assist in unraveling specific mechanisms underlying clinical aggressiveness in poor-prognostic stereotyped subsets, with far-reaching implications for understanding their clonal evolution and implementing biologically oriented therapy.
Keywords: fosfoproteiny; nádorové biomarkery; malý jaderný ribonukleoprotein U2; Baculoviral IAP Repeat-Containing 3 Protein; Prognosis; Biomarkers, Tumor; Humans; Polymerase Chain Reaction; Mutation; následné studie; Cohort Studies; Phosphoproteins; Leukemia, Lymphocytic, Chronic, B-Cell; míra přežití; ubikvitinligasy; prognóza; Follow-Up Studies; sestřihové faktory; RNA Splicing Factors; receptor Notch1; Inhibitor of Apoptosis Proteins; Ribonucleoprotein, U2 Small Nuclear; inhibitory apoptózy; Survival Rate; chronická lymfatická leukemie; polymerázová řetězová reakce; Receptor, Notch1; buněčný inhibitor apoptózy 2; Ubiquitin-Protein Ligases; DNA, Neoplasm; lidé; kohortové studie; DNA nádorová; mutace